2018
DOI: 10.1039/c8nr01347k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 2D nanomaterials with switchable binding to investigate graphene–bacteria interactions

Abstract: Graphene and its derivatives have recently attracted much attention for sensing and deactivating pathogens. However, the mechanism of multivalent interactions at the graphene-pathogen interface is not fully understood. Since different physicochemical parameters of graphene play a role at this interface, control over graphene's structure is necessary to study the mechanism of these interactions. In this work, different graphene derivatives and also zwitterionic graphene nanomaterials (ZGNMs) were synthesized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Although GS NSs were chosen as a typical 2D NM for this study, more 2D NMs should be similarly screened for their antibacterial potential. Chemical modifications may also influence the antibacterial activity of 2D NMs . Adeli et al provided a new insight into the interactions between graphene and bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GS NSs were chosen as a typical 2D NM for this study, more 2D NMs should be similarly screened for their antibacterial potential. Chemical modifications may also influence the antibacterial activity of 2D NMs . Adeli et al provided a new insight into the interactions between graphene and bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their exceptional physical and chemical properties, 2D nanomaterials (2D NMs) have attracted extensive attention in biomedical applications such as cancer phototherapy, biosensors, and antimicrobial activity . Many 2D NMs such as graphene and derivatives, black phosphorus, MoS 2 , and Ti 3 C 2 T x MXenes exhibit antibacterial activity, which substantially reduces the possible development of bacterial drug resistance. In this work, we developed new 2D GS NSs ( Figure a) with antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…In another study [167], when bovine serum albumin (BSA) or tryptophan (Trp) molecules were noncovalently adsorbed on GO basal planes, the occupation could cause GO's deactivation against bacteria, suggesting the availability of GO basal planes in the cytotoxicity against bacteria. Recently, Haag et al [168] confirmed that the antimicrobial property of graphene was very relevant to both its sharp edges, basal planes and tight agglomeration by studying the interactions between functionalized graphene derivatives and bacteria.…”
Section: Mechanisms Of Antibacterial Activities Of Graphene-based Nanmentioning
confidence: 99%
“…Zhang et al reported that cytotoxicity is size dependent of GO lateral dimension. [37] Nevertheless, antibacterial activity of GO is still controversial since contradictory studies can be found and discussed in the literature. [26] Likewise, antibacterial activity of GO (important to consider while designing pathogen biosensors) has been reported to be size-dependent, which may be able to compromise bacterial membrane integrity via oxidation stress, see Figure 2C.…”
Section: Lateral Sizementioning
confidence: 99%